Effect of thermal cycling on microleakage between hard chairside relines and denture base acrylic resins - Giampaolo, Eunice Teresinha [UNESP]; Jorge, Janaina Habib [UNESP]; Machado, Ana Lucia [UNESP]; Pavarina, Ana Claudia [UNESP]; Vergani, Carlos Eduardo [UNESP] (Wiley-Blackwell, 2011)
Objectives:Microleakage is a pre-stage of debonding between hard chairside relines and denture base acrylic resins. Therefore, it is important to assess them with regard to the longevity of the relined denture. This study investigated the effect of thermal cycling on the microleakage at the interface of three hard chairside reline resins and three denture base resins.Material and methods:Rectangular bars (12 mm x 3 mm x 3 mm) of Lucitone 550, Acron MC and QC 20 were made and relined with Kooliner, Tokuyama Rebase Fast II and Ufi Gel Hard, Lucitone 550, Acron MC and QC 20 resins. Specimens were divided into one control and two test groups (n = 10). In specimens of the control group, the microleakage was performed after the reline procedure. In Test Group 1, the specimens were stored for 24 h in distilled water at room temperature and in Test Group 2; the specimens were thermal cycled from 5 to 55 degrees C for 5000 cycles with a 30-s dwell time. Subsequently, all specimens were immersed in 50% silver nitrate solutions for 24 h. All specimens were sectioned longitudinally into three fractions and the lateral sections were examined (n = 20). Silver nitrate stain penetration was examined under a stereoscopic lens with x30 magnification, and the images were captured. Leica Qwin image analysis software was used to determine microleakage at the interface of the materials. Data were analysed using the Kruskal-Wallis test at a 95% level of significance.Results:For all cycles, there were no statistically significant differences between thermal cycled and non-thermal cycled groups (p > 0.05).Conclusion:It can be concluded that thermal cycling had no effect on the microleakage.
Keywords: thermal cycling; microleakage; acrylic resins